Canada's Trial Courts : Two Tiers or One? - Russell, Peter H. (Book collections on Project MUSE., 2007)
Featuring distinguished contributors from a variety of disciplinary backgrounds, Canada's Trial Courts offers a comprehensive and up-to-date examination of an important but neglected issue that ultimately has a profound impact on the quality of justice that Canadians experience.